1999
DOI: 10.1002/(sici)1099-1379(199911)20:6<783::aid-job923>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Attachment behavior and health: relationships at work and home

Abstract: SummaryThis article examines the relationships between interpersonal attachment orientations, health, and social support. Four hypotheses speci®ed relationships between three interpersonal attachment orientations (interdependent, counterdependent, and overdependent), physical and psychological symptoms, and social support. Data were collected from 297 students, the majority of whom were also full-time employees. An interdependent orientation was negatively related to social dysfunction. Counterdependent and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…Historically, researchers have used a categorical approach (e.g., The Adult Attachment Interview; Main, Kaplan, & Cassidy, 1985; The Relationships Questionnaire; Bartholomew & Horowitz, 1991;Hazen & Shaver, 1987) or used a A c c e p t e d M a n u s c r i p t Attachment, Civility, and Burnout-18 three-dimensional approach (i.e., interdependent, counterdependent, and overdependent;Joplin et al, 1999). Fraley and Waller (1998) found the two dimensions mapped onto the avoidance and anxiety dimensions of Bartholomew's model (Griffen & Bartholomew, 1994b).…”
Section: Measurement Of Attachmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Historically, researchers have used a categorical approach (e.g., The Adult Attachment Interview; Main, Kaplan, & Cassidy, 1985; The Relationships Questionnaire; Bartholomew & Horowitz, 1991;Hazen & Shaver, 1987) or used a A c c e p t e d M a n u s c r i p t Attachment, Civility, and Burnout-18 three-dimensional approach (i.e., interdependent, counterdependent, and overdependent;Joplin et al, 1999). Fraley and Waller (1998) found the two dimensions mapped onto the avoidance and anxiety dimensions of Bartholomew's model (Griffen & Bartholomew, 1994b).…”
Section: Measurement Of Attachmentmentioning
confidence: 98%
“…One solution to this question has been to explicitly define and assess secure attachment as a distinct construct in addition to assessing indicators of attachment anxiety and attachment avoidance (e. g., Joplin, Nelson, & Quick, 1999). An alternative solution follows the work of Fraley and Waller (1998) by using both positively worded and negatively worded items to assess anxiety and avoidance on two dimensions, Fraley and Waller found strong support for a two-dimensional model of adult attachment.…”
Section: Attachment At Work De Vriesmentioning
confidence: 99%
“…Nurses with insecure attachment styles reported less hope and those with avoidant attachment reported being less healthy. Joplin et al (1999) found similar results in a sample of students who worked full time. Individuals with higher levels of avoidant attachment reported experiencing psychological problems in addition to insomnia and social dysfunction.…”
Section: The Mediating Role Of Attachment Insecuritymentioning
confidence: 99%
“…Within the voluminous literature rooted in attachment theory (Ainsworth, Blehar, Waters, & Wall, 1978;Bowlby, 1969Bowlby, /1982Bowlby, , 1973Bowlby, , 1980, a fledgling sub-strand is developing, concerned with adults' attachment orientation or style as this bears on their functioning at work (e.g., Elliot & Reis, 2003;Hazan & Shaver, 1990;Joplin, Nelson, & Quick, 1999;Mikulincer & Shaver, 2007;Schirmer & Lopez, 2001;Simmons, Gooty, Nelson, & Little, 2009). Most researchers working in this area have tended to treat attachment as if it were a personality-like trait that extends across contexts, and attachment orientation or style (terms used interchangeably in this paper) has tended to be measured using one or another of the existing instruments originally developed to assess attachment in the context of romantic or other personal dyadic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…One exception to this approach to measurement, the Self-Reliance Inventory (Quick, Joplin, Nelson, & Quick, 1992), was originally developed from probative interviews with successful executives, and subsequently refined drawing from content generated by management graduate students (Joplin et al, 1999). In their 1999 paper, these researchers reported finding no statistical relationships between attachment orientation and performance but, as they noted, academic performance ''may not be an effective proxy for performance at work'' (Joplin et al, 1999, p. 790).…”
Section: Introductionmentioning
confidence: 99%